Some ecological aspects of free-living Haemaphysalis juxtakochi Cooley, 1946 (Acari: Ixodidae) in Panama - García G., Gleydis; Castro D.F., Angélica; Bermúdez Castillero, Sergio Eduardo; Nava, Santiago (Universidad de Córdoba (Colombia), 2017)
Objective. To describe the seasonal variation and perform a comparative analysis on habitat preference of Haemaphysalis juxtakochi in Panama. Materials and methods. Ticks were collected from the vegetation, using a white cloth, between January 2009 and March 2010, in four site located in Summit Municipal Park (SMP), two in wooded area (WA) and two in grasslands (GR).The ticks were determined as larvae, nymphs and adults of H. juxtakochi. The number of ticks collected in each area was employed to describe the seasonal distribution of both immature and adult stages, and the non-parametric Mann-Whitney U test. Results. A total of 2.338 ticks in WA and 560 ticks in GR were collected. The major peak of adults from May to July, nymphs peaked from January to April and the peak of larvae abundance from December and January. There was a significant difference in the number of ticks collected in the two areas for each tick stage (larvae, mean number (MN) in WA 120.14, MN in GR 57.07, P: 0.02; nymphs, MN in WA 46.42, MN in GR 16.38, P: 0.018; adults, MN in WA 6.64, MN in GR 1.78, P: 0.02). Conclusions. The results suggest that H. juxtakochi maintains a one-year cycle in the study areas. This cycle would be characterized by the immature population peaks in the dry season; while adults are distributed throughout year, with a peak in the transition from the rainy and dry. Moreover, H. juxtakochi was more abundant in forests than in grasslands, which could lead to a better adaptation to forested conditions.